Evaluación del efecto de distintos abonos en el rendimiento de la mezcla forrajera establecida Rye grass (Lolium perenne), Alfalfa (Medicago sativa), Trébol blanco (Trifolium repens) y Pasto azul (Poa pratensis) en la Comunidad San Ignacio, Parroquia Toacazo, Cantón Latacunga, Provincia de Cotopaxi 2017-2018 - Bohórquez Flores, Alex Patricio (2018)
The following research project carried out the evaluation of the effects of an organic-mineral fertilizer (Pasture milk), organic fertilizer (cow manure compost) and a humus organic mineral in the established forage mix composed of Rye grass (Lolium perennial), Alfalfa (Medicago sativa), White clover (Trifolium repens) and Blue Grass (Poa pratensis), that are grown in the community of San Ignacio, Toacazo Parish, Canton Latacunga, where the effect of the different fertilizers mentioned was evaluated, measuring the following variables: height of the species, weight in green and dry weight, and bromatological composition, in order to determine the most appropriate treatment that will help the community to improve its pasture production and allow us to compare the production costs of each of the treatments. Of the treatments evaluated, organic-mineral fertilizer based on humus (T3) presented the best results in height (38.90 cm of the first cut and 53.10 cm of the second cut), green weight (179.052 kg of the first cut and 401.67 kg of the second cut), dry weight (10043.06 kg of the first cut and 17586.87 kg of the second cut), in bromatological composition (humidity: 76.90%, ash: 10.75%, fat: 2, 65%, protein: 16.94%, fiber: 27.86%, net energy for lactation: 41.79% of the second cut or final) The results obtained in this research in the proposed sector will serve to propose alternatives that reduce the use of chemical products for sustainable production